Perbandingan Hukum Antara Indonesia dan Uni Eropa Terkait Pengaturan Anti-Dumping - Angelia, Novita (Tribuere, 2022)
Looking at the different positions between Indonesia and the European Union, where the EU is a customs union with a single trade and tariff policy, then this research and writing aims to describe and analyze how the anti-dumping regulation is based on the law in Indonesia and in the EU as well as how the differences and similarities are fundamental to the anti - dumping regulations in Indonesian and European Union law. Using the type of normative law research with comparative methods. Based on the results of research and analysis, the anti-dumping arrangements in Indonesia and the European Union have been loaded and aligned with Article VI of the GATT and the Anti-Dumping Agreement. Indonesia and the European Union have chosen a different strategy, in which the EU regulates provisions that are beyond international obligations regarding various aspects of procedural and substantive methodology in anti-dumping investigations, which are not included in the Indonesian antidumping arrangements. Both sides have differences in anti-dumping structures in the context of the institutional framework, the establishment of the constructed normal value, and the involvement of small and medium-sized enterprises. However, Indonesia and the European Union have similar provisions to determine export prices and losses, standing for domestic industry as well as ensuring anti-dumping measures do not create conflicts of interest.